Monitoring of radionuclides in carbon steel blooms produced by EAF process - Sofilić T.; Barišić D.; Sofilić U.; Živković J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Because natural and artificial isotopes in steel might originate from steel scrap or from the residue of the material that was used in the technological process, thus monitoring especially artificial radionuclides 60Co, 137Cs and 192Ir deserve special attention. The analysis by g-spectrometry has been applied to determine the presence of natural isotopes 40K, 226Ra, 232Th and 238U as well as of the artificial isotope 60Co, 137Cs and 192Ir and their activity in the produced steel round blooms in the Steel Mill of CMC Sisak d.o.o. At the same time the content of radionuclides in the other materials (ferroalloys, bauxite, fluorite, lime, coke, graphite electrodes, refractory blocks) used in the same steel making process was investigated. The measured values regarding the presence of individual isotopes and their activity in steel were as follows: 40K all values were less than 1.6 Bqkg-1; 232Th all activities values were less than 0.02 Bqkg-1; 226Ra all activities values were less than 0.01 Bqkg-1; 238U all activities values were less than 1.10 Bqkg-1; 60Co all activities values were less than 0.02 Bqkg-1; 192Ir all activities values were less than 0.02 Bqkg-1 and 137Cs all activities values were less than 0.30 Bqkg-1.